Tem que se cuidar: saberes e práticas de gestantes atendidas em uma unidade básica de saúde de Santa Maria/RS - Sanfelice, Cheila (2011)
Pregnancy is a culturally identified period by diverse knowledge and practices that involve the pregnant and the baby care, being a singular experience to the woman and the family. The knowledge and care practices related to the pregnancy vary in the different cultures and can diverge from the technical-scientific conceptions from the health professionals. This study is based upon the concept of culture from Clifford Geertz and aimed to get knowledge and care practices that surround the pregnancy of women attended in a Unity of Basic Health. For so, a descriptive-exploratory field research with a qualitative approach was developed. Sixteen pregnant women attended in the nursing prenatal at the Kennedy Sanitary Unity in Santa Maria /RS. The setting was the nursing office at the aforesaid unity and at the pregnant houses. The data collection happened between March and June of 2011, through a semi structured interview and observation of the participant. A thematic analysis was done to have the data investigation. The realization of this study was approved by the Center of Permanent Education from the Municipal Health Bureau from Santa Maria and by the Committee of Ethics in Research from the Federal University of Santa Maria. As a result, the theme Take care of yourself: knowledge and care practices of pregnancy and the three subthemes: The care pregnant women know and do during pregnancy , The construction of knowledge around the care in pregnancy and the popular myths around pregnancy emerged. It was evidenced that during pregnancy, women adopt many care practices to keep hers and the baby well-being. Such practices comprise the prenatal follow-up, nourishment, physical and emotional well-being and some prohibitions. The knowledge that the participants of this study have about pregnancy care comes from the family knowledge, the social environment, and the media and from the health professionals. They also know some myths about pregnancy, mainly the ones related to some practice that can harm the baby growth. The findings of this study indicate the importance of knowing the pregnant cultural context in order to give an appropriate service according to their needs. This way, it is hope to contribute such as for nurses, as for the other health professionals, in the quality improvement of prenatal attention, looking for the valorization of popular knowledge and practices about pregnancy